The behaviour of producer prices: some evidence from the French PPI micro data - Erwan Gautier (European Central Bank (ECB), 2006)
This paper provides some new empirical features on price setting behaviour for French producers using micro data underlying the producer and business-services price indices over the period 1994-2005. Some crucial methodological issues on the collection of producer prices are raised. Then, the main features of producers' price setting are presented: producer prices are modified quite frequently and by small amounts. A high heterogeneity across sectors is also observed: business-services prices change less often than industrial producer prices. The data lend some support to predictions of both time- and state-dependence models: Taylor contracts are not unusual but prices also respond to the changes in the firm's economic conditions. Nevertheless, time-dependent models are shown to be the most relevant theories to explain the producer price rigidity.
Keywords: E31; D43; L11; L16; 330; frequency of price change; price duration; Price stickiness; producer price index; Preismanagement; Preisniveau; Verbraucherpreisindex; Frankreich